VALUE ORIENTATIONS AS FACTORS OF MOTIVATION OF LEGAL ACTIVITY IN THE FIELD OF PUBLIC ADMINISTRATION - Blikhar, Mariia (Socio-economic relations in the digital society, 2025)
In the article, within the framework of administrative and legal discourse, the author examines the content of value orientations as factors of motivation of legal activity in the field of public administration. It is found that the value aspects of motivation of legal activity are determined primarily by the level of understanding of the importance of its parameters which should record the state of lawyers’ awareness of the urgent need to form the features of legal behaviour which is determined by the factors which are considered as priorities in meeting the important needs of the individual in the relevant specific historical and social conditions. It is substantiated that the process of formation of legal motivation is a phenomenon which reflects important processes which can motivate a person to act within the framework of involvement of internal reserves of a personal nature, where psychological factors play a priority role, and a person effectively determines his/her organization and activity and contributes to the active satisfaction of personal needs, the issues of formation and realization of values occupy an important place. In analyzing this issue, the author states that values as criteria for evaluating real phenomena give an idea of how the world should be organized and what a person should be like. They define the goals to be pursued by an individual, group or society, the main means of achieving them, the meaning of purposeful activity, and regulate social relations and internally motivate activities in the field of public administration. Furthermore, they are not subject to doubt and are the standard and ideal for people who adhere to them. In this context, it is proved that the essential characteristics of human motivation are determined by a peculiar combination of subjectivities of this process with factors of external influence which are of a social nature, which is manifested in the natural process of combining personal activity with social support and incentives. In addition, the author notes that legal values in the formation of motivation for legal activity are realized as a phenomenon of the spiritual order since they play the role of a regulator exclusively as a manifestation of the subjective side of human activity. That is, it is summarized that values form the main priorities of human activity, inspire to perform actions which can maximally satisfy the needs of human existence, realizing the inner conviction that one’s behaviour is right.